The internal effects of ASEAN external relations - Venzke, Ingo; Thio, Li-Ann 1968- (Integration through law : the role of law and the rule of law in ASEAN integration, 2016)
"Starting with a typology of ASEAN external agreements, the authors go on to provide an original reading of plurilateral agreements as 'joint' agreements. The book then offers both a clarification of the effects - direct or indirect - of external agreements within the legal orders of ASEAN Member States, and an explanation of the effects of external agreements within the legal regime of ASEAN. The authors conclude with a discussion of the role of ASEAN centrality and the role of the secretariat in shaping it"...